Dental age in patients with Down syndrome - de Moraes, Mari Eli Leonelli [UNESP]; Bastos, Michelle Silva [UNESP]; dos Santos, Luis Roque de Araujo [UNESP]; Castilho, Julio Cezar de Melo [UNESP]; de Moraes, Luiz Cesar [UNESP]; Medici Filho, Edmundo [UNESP] (FapUNIFESP (SciELO), 2007)
The aim of this research was to evaluate dental age in 102 patients with Down Syndrome, using panoramic radiographs. A software program developed by the Discipline of Radiology, School of Dentistry of São José dos Campos, São Paulo State University (UNESP), was used. A table of mineralization chronology of permanent teeth among Brazilians conceived by Nicodemo, Moraes and Medici Filho was used within the software. Statistical analysis of the results showed that 70.91% of the males land 61.21% of the females presented advanced dental age. Only 32.09% of the males and 39.79% of the females presented delayed dental age. Regarding the differences between the dental and chronological ages, two thirds of the males and females presented dental age with differences of up to 12 months, which means that they can be considered to be within normal standards, whereas only 18.87% of the males and 10.21% of the females presented dental age outside normal standards, with differences of over 24 months. In conclusion, the majority of the patients with Down Syndrome were considered to be within the normal standards of mineralization chronology.
Keywords: Age determination by teeth; Down syndrome; Radiography, panoramic; Tooth calcification; adolescent; age determination; child; dental care; dentition; female; human; male; molar tooth; panoramic radiography; physiology; preschool child; radiography; sex difference; tooth development; Adolescent; Age Determination by Teeth; Child; Child, Preschool; Dental Care for Disabled; Dentition, Permanent; Down Syndrome; Female; Humans; Male; Molar, Third; Radiography, Panoramic; Sex Factors; Tooth Calcification